A Hierarchical Integrated Model of Self-Regulation - Blair, Clancy; Ku, Seulki (Frontiers in Psychology, 2022)
We present a hierarchical integrated model of self-regulation in which executive function is one of five distinct components. The model is comprised of cognitive, emotional, behavioral, physiological, and genetic levels which are reciprocally and recursively related. We present empirical support for the model, primarily from a single longitudinal study with good measurement at each level of the model. We find that the model is consistent with current thinking on related topics such as cybernetic theory, the theory of allostasis and allostatic load, and the theory of skill development in harsh and unpredictable environments, referred to as “hidden talents”.